The evolution of hereditary cancer genetic counselling: mainstreaming, service redesign and patient experience in Lynch syndrome - Kelly Kohut; Sarah Cable; Alekhya Ashokan; Stefania Vicari; Hannah Ditchfield; Julie Young; Ben Bux; Fiona Lalloo (Familial Cancer, 2026)
Abstract Genetic counselling for hereditary cancer predisposition has evolved substantially over more than three decades, driven by advances in genomic technologies and the growing use of tumour and germline testing. These developments have expanded access to hereditary cancer testing, treatment and prevention, while also introducing new clinical, psychosocial and system-level challenges. This review examines the transition from traditional specialist-led genetic counselling to mainstreamed testing pathways. Using Lynch syndrome as a paradigm, we explore how service redesign, personalised risk communication and patient experience intersect in contemporary hereditary cancer care. This invited review synthesises clinical, academic and patient perspectives on the evolution of hereditary cancer genetic counselling. Lived experiences of Lynch syndrome were incorporated through patient and public involvement contributors involved in manuscript development and interpretation. Mainstreamed testing has expanded access to genomic information and strengthened opportunities for cascade testing and prevention within families. However, it has also increased testing volumes, complexity of results interpretation and reliance on non-genetics clinicians. As a result, effective care requires close coordination between genetics and cancer services, alongside support for shared decision-making, family communication and psychosocial needs. This review uniquely integrates clinical evidence and lived experience to highlight how mainstreaming has transformed the delivery of hereditary cancer genetic counselling but not the need for specialist genetics expertise. Lynch syndrome illustrates how genomics can be integrated into routine cancer care while maintaining personalised counselling and family-centred follow-up. These principles are relevant across hereditary cancer predispositions and inform the future development of genetic counselling services.